TALK SHOW EDUKATIF PARTISIPATIF: MENINGKATKAN LITERASI HAK PRIVASI DAN ETIKA PUBLIKASI DI MEDIA SOSIAL BAGI MAHASISWA - Sandira, Nur Fadilah Ayu; Sarah, Nulthazam; Ridhoh, M. Yunasri; Iswardhani, Indri; Nasir, Sri Astuti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service activity aims to improve students’ understanding of privacy rights and ethical publication on social media. The method used was a participatory educational approach through an interactive talk show conducted as part of Edufair 2024 at Universitas Negeri Makassar. Students were actively engaged in open discussions addressing digital ethics and privacy protection. The results indicate an increased awareness among participants to use social media more wisely and responsibly. They began to consider ethical aspects before sharing content and understood the potential legal consequences of privacy violations. This activity contributed positively to shaping students’ critical attitudes toward digital content and encouraged the application of ethics in their daily online behavior.